Salmonella diversity and antimicrobial resistance in Burkina Faso: An investigation of strains from various sources - Kagambèga A., Bouda S. C., Bako E. , Cissé H. , Barro N, Haukka K. (African Journal of Pig Farming, 2023)
Epidemiologic and traceback evidence of Salmonella infection is not much in many developing countries including Burkina Faso. This study investigates the antimicrobial resistance and distribution of Salmonella serotypes isolated from diverse sources in Burkina Faso. 615 Salmonella serotypes isolated from beef meat, poultry carcasses, poultry, swine, cattle, hedgehog, fish, salad, channel and humans from 2009 to 2011 were analyzed to identify their diversity and distribution among the samples. The Salmonella strains were subjected to antimicrobial sensitivity tests using disk diffusion methods, were analyzed and classified into 110 serotypes, with the most prevalent serotype being Derby (91/615) found in beef meat, poultry carcasses, poultry and fish; Muenster (48/615) found in cattle, swine, hedgehog, poultry, human and fish; Chester (38/615) found in poultry carcasses, swine and poultry feces; Hato (32/615) found in beef meat, poultry carcasses, cattle and poultry; Drac (30/615) found in cattle, hedgehog and fish; and Typhimurium (21/615) found in cattle, poultry, human and fish. Among the 615 Salmonella strains, 94% (581/615) were resistant to one or more antibiotics; resistance to streptomycin was the most common. The resistance pattern, Str-Sul-Tet, Str-Tet and Str-Sul was dominant and found in 80% of the strains. About 3% of the strains were resistant to 5 or 6 antibiotics; their resistance pattern is amp-str-sul-tet-tmp or amp-chl-str-sul-tet-tmp. One Salmonella strain, S. Kentucky isolated from human stool was resistant to eight antibiotics; the resistance pattern is amp-strsul-tet-cip-gen-nal-mec. Findings from this study can help define the guidelines for basic surveillance system of Salmonella and other enteropathogenic bacteria circulating among humans, animals, food and environment.